Lyme disease - Williams, Mary E. , 1960- (Perspectives on diseases and disorders, 2012)
"Lyme Disease: Understanding Lyme Disease; Debates Surrounding Lyme Disease; Experiencing Lyme Disease"-- Provided by publisher